(3SDGd GHf CHj TQja aj OjQ Ugjhf hGdEaQfLs - (3GHf CHj TQja , eMeO Hf eMeO Hf CHj HcQ Hf Ydj GdebOSj, ceGd GdOjf CHh GdeYGd,J (B906 (3g` s
(3ChdgG (B:s
(3SFdJ ai Pi GdMLI SfI KeGfeGFI hNeS hJSYjf HeG UhQJg ai hGbYI hbYJ HHjJ GdebOS hgh Cfg HGdbOS ecGf jbGd dg Ugjhf hgh OjQ jCJjg ef HdGO GdaQfL s
(3BNQgG (B:s
(3aEPG CbQ GdcaGQ Ydjge de jZOge GdJbQjQ edcG s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B53 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B200s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B226 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs